UPAYA PENINGKATAN MINAT DAN PEMAHAMAN SISWA KELAS 4 PADA MATERI AKU DAN KEBUTUHANKU MELALUI MEDIA AUDIO LAGU ANAK - Sri Marwati; Septiana Widyaningrum; Moh. Rusnoto Susanto; Heri Maria Zulfiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to enhance students’ interst and understanding of the material “Me and My Needs” using children’s song audio media. This research is a Classroom Action Research (CAR) conducted in three cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The subject of the study were fourth-grade students at SD Negeri 1 Wonokerso. Data were collected through interviews, observations, questionnaires, and student comprehension tests. The results of the study indicate that the use of song audio significantly increased students’ interest dan undersatanding of the tought material. In the first cycle, student interest began to rise although the comprehension remained relatively low. In the second cycle, there was a significant improvement in both interest and comprehension. The third cycle showed optimal results, where almost all students demonstrated high interest and good comprehension of the material. Therefore, the use of song audio media is proven to be effective in enhancing students’ interest and understanding of the material “Me and My Needs”. The implementation of this strategy is recommended as an innovative and enjoyable alternative for primary school learning.